2015
DOI: 10.1007/s00068-015-0519-7
|View full text |Cite
|
Sign up to set email alerts
|

Open distal tibial shaft fractures: a retrospective comparison of medial plate versus nail fixation

Abstract: ORIF leads to higher rates of nonunion and significantly increases the odds of developing a complication compared with IMN for open distal tibia fractures. This is the first study investigating complication rates based on surgical approach in a large cohort of patients with exclusively open distal tibia fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 20 publications
0
22
0
1
Order By: Relevance
“…The patient was treated with surgical debridement and hardware removal to decrease biofilm burden. In this case, initial treatment with medial plate may have increased the risk for non-union and wound-healing complications, but previous literature has not demonstrated an increased patient risk for infection 12–14. Biofilm formation, particularly with regards to orthopaedic devices, has been proposed in the literature as an important feature in the maintenance of infection, which also contributes to the difficult nature of eradication in these reported infections 8 15.…”
Section: Discussionmentioning
confidence: 83%
“…The patient was treated with surgical debridement and hardware removal to decrease biofilm burden. In this case, initial treatment with medial plate may have increased the risk for non-union and wound-healing complications, but previous literature has not demonstrated an increased patient risk for infection 12–14. Biofilm formation, particularly with regards to orthopaedic devices, has been proposed in the literature as an important feature in the maintenance of infection, which also contributes to the difficult nature of eradication in these reported infections 8 15.…”
Section: Discussionmentioning
confidence: 83%
“…The advantages of applying open reduction and internal xation were that the fracture site could be exposed su ciently and the reduction could be ful lled anatomically under direct vision. Researchers [3,[15][16][17] reported that the deformed union rate of fractures after plate xation was less than 10%, but the risk of postoperative complications with soft tissues was higher, including super cial infections, deep infections, delayed wound healing, and necrosis of soft tissues. In the early 1940s, the intramedullary nail system was introduced to treat tibial shaft fractures, which can reduce the deformity union for tibial fracture and decrease the formation of pseudo-articular joints after the surgery, meanwhile promote the ossi cation of fractured callus.…”
Section: Discussionmentioning
confidence: 99%
“…With the increase in high energy trauma and osteoporosis, the incidence of open fractures as well as complex fracture patterns involving a large segment of distal tibia has increased. 1,13 The soft tissue envelope over the distal tibia is thin with limited vascularity and is prone to complications like wound dehiscence and infection. The management of these fractures is dictated by the condition of the soft tissues and a two staged approach with initial spanning external fixation is often necessary.…”
Section: Discussionmentioning
confidence: 99%